Identification of core gene-gut microbiome associations in diverticulitis patients through a two-sample mendelian randomization and bioinformatics-based investigation - Wende Hao; Zhenjun Wang; Huachong Ma (Global Medical Genetics, 2025)
Background: Previous studies have suggested a potential link between the gut microbiota and diverticulitis. However, the causal relationships as well as underlying mechanisms remain unclear. Methods: The causal effects of gut microbiota on diverticulosis & diverticulitis was assessed using two-sample Mendelian randomization analysis. The sensitivity analyses were also performed. We then used integrative bioinformatics tools to identify core genes associated with diverticulitis and explore their potential mechanisms and therapeutic targets. Results: Inverse variance weighted analysis indicated that Family XIII (OR=0.281, 95 % CI: 0.093–0.853, P = 0.025) and Defluviitaleaceae UCG-011 (OR=0.382, 95 % CI: 0.162–0.898, P = 0.027) were negatively associated with the risk of diverticulosis and diverticulitis, whereas Oscillospira (OR=3.514, 95 % CI: 1.146–10.779, P = 0.028), Ruminiclostridium 6 (OR=2.629, 95 % CI: 1.093–6.322, P = 0.031), Lachnoclostridium (OR=2.458, 95 % CI: 1.014–5.962, P = 0.047), and Desulfovibrionales (OR=2.157, 95 % CI: 1.038–4.480, P = 0.039) were positively associated with disease risk. The sensitivity analyses validated these correlations. Through SNP annotation, we identified 23 host genes associated with pathogenic gut microflora in diverticulosis and diverticulitis, and retrieved 213 diverticulitis-related genes from GeneCards. Intersection analysis revealed LRRC4C as the sole shared gene. Differential expression analysis further showed that LRRC4C was significantly downregulated in diverticulitis compared to infective colitis. Finally, eight candidate drugs were identified as potential inducers of LRRC4C expression. Conclusion: The research revealed potential causal relationships between gut microbiota and diverticulitis. LRRC4C was identified as a core gene associated with pathogenic microbial traits in diverticulitis, and candidate therapeutic drugs for diverticulitis based on LRRC4C were predicted, offering novel strategies for the prevention and management of the disease.